Theoretical Basis of Teaching English Grammar - Qodirova Dilnoza Mamadiyorovna; Daminova Mashhura Zafarovna; Khalikova Dildora Yadullayevna; Niyozova Shoira Toirovna (Research Parks Publishing LLC, 2021)
This article aims to identify the various components of English grammar that define the theoretical foundations of English grammar in teaching secondary school pupils. In addition, the origin of grammar and the harmony of form and meaning in grammar, the importance of grammar in language are discussed and explained.